Garnet-doped composite polymer electrolyte with high ionic conductivity for dendrite-free lithium batteries. (August 2019) - Xu, Linghong; Li, Guibin; Guan, Jianxin; Wang, Lulu; Chen, Jitao; Zheng, Junrong
Graphical abstract: Highlights: Li6.4 La3 Zr1.4 Ta0.6 O12 -doped composite polymer electrolyte (CPE) membrane for high performance lithium batteries. Excellent mechanical properties, electrochemical stability and high ionic conductivity. The CPE membrane surprisingly restrains the growth of Li dendrites. LiFePO4 /Li batteries using the CPE exhibit excellent cycling performance and superior rate capability. Abstract: Solid polymer electrolytes are promising candidates to replace the extensively used flammable liquid electrolytes in lithium batteries. However, pure polymer electrolytes seldom meet practical requirements because of their relatively low ionic conductivity and poor mechanical properties. Herein, we report a garnet (Li6.4 La3 Zr1.4 Ta0.6 O12, LLZTO)-doped composite polymer electrolyte (CPE) membrane for high performance lithium batteries. The CPE is composed of poly(vinylidene fluoride- co -hexafluoropropylene) (PVDF-HFP) and poly(ethylene glycol) methyl ether methacrylate (POEGMA) polymer with the addition of ceramic particles LLZTO. It not only has high ionic conductivity of 1.00 × 10 −3 S cm −1 after the activation of liquid electrolyte at room temperature, but also surprisingly restrains the growth of Li dendrites. Its electrochemical stability window is up to 4.7 V (vs. Li + /Li). Moreover, LiFePO4 /Li batteries using the CPE exhibit excellent cycling performance and superior rate capability.